COMPRESSIBILITY EFFECTS ON DISTRIBUTIONS OF PRESSURE AND LIFT COEFFICIENTS (Journal of Sciences & Technology, 2017)
Reduce energy consumption of airplanes, or enhance the aerodynamic performance of compressors and turbines by reducing drag, or increasing lift is a major challenge for many institutions specializing in aerodynamics [1, 2]. One way to achievethis, isconsidered the study of compressible potential flow compared to incompressible potential flow [3], Outside the boundary layer, to study the effects of compressibility and the control parameters. And the pressure coefficient and lift distributions around the NACA 0012 profile, NACA 0015 and NACA 0018 were studied and presented in terms of the Mach number, angle of attack and the relative thickness of the profiles.